Does risk aversion matter for foreign asset holdings of pension funds: The case of Poland - Radosław Kurach; Daniel Papla (Comparative Economic Research. Central and Eastern Europe, 2014)
In this study we explore the issue of foreign assets in mandatory pension funds portfolios. First we provide an overview of the regulatory policies regarding international assets and indicate the externalitieswhich may account for the observed differences among the CEE states. Then, taking the perspective of portfolio theory, we run a simulation study to measure the diversification benefits that may be achieved by greater international asset allocation. By applying the specific constraints and exchange rate volatility to our optimization procedure, the study reflects the perspective of the Polish pensioner. However, the findings regarding risk aversion intensity and the discussed directions of further research should be of a universal character.
Keywords: 330; pensions funds; currency risk; international portfolios